Pengembangan Bahan Ajar Menulis untuk Pelajar BIPA Tingkat Pemula - Izhhar Amala Zein; Gatut Susanto; Kusubakti Andajani (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: This development research aims to produce teaching material of writing for beginner students of BIPA. The development procedure is carried out by the stages of goal setting, designing, developing and disseminating the product. The development procedure was adapted from Thiagarajan's four-D Models. The results of the development indicated that three aspects were described, namely (1) the content of teaching materials; (2) language; and (3) the presentation based on the results of the validation test in accordance with BIPA experts and BIPA practitioners in the use of products, it can be concluded that writing teaching materials for beginner students of BIPA are feasible to be used.Abstrak: Penelitian pengembangan ini bertujuan untuk menghasilkan bahan ajar menulis bagi pelajar BIPA tingkat pemula. Prosedur pengembangan dilakukan dengan tahapan penetapan tujuan, perancangan, pengembangan, dan diseminasi produk. Prosedur pengembangan tersebut diadaptasi dari four-D Model.  Hasil pengembangan menunjukkan bahwa tiga aspek yang digambarkan, yaitu (1) isi bahan ajar; (2) kebahasaan; (3) penyajian berdasarkan hasil uji validasi pakar BIPA dan praktisi BIPA dalam penggunaan produk dapat disimpulkan bahan ajar menulis untuk pelajar BIPA tingkat pula ini layak digunakan.